MODEL PEMBELAJARAN PROJECT BASED LEARNING (PjBL) UNTUK MELATIH KETERAMPILAN KOLABORASI SEBAGAI KETERAMPILAN ABAD 21 DAN MENINGKATKAN HASIL BELAJAR MAHASISWA (JS (JURNAL SEKOLAH), 2025)
Absract: Collaboration skills are 21st century skills that are very important to be trained to learners, especially to students as a provision for entering the world of work.. Collaboration skills can be trained in learning with a continuous process through the right learning model and teaching materials. This study aims to see the effect of the Project Based Learning (PjBL) learning model using teaching materials developed with the PjBL model on collaboration skills and improving student learning outcomes in the Kapita Selecta Chemistry course. In addition, a correlation test was conducted to see if there was a positive and significant correlation between collaboration skills and improved student learning outcomes. This study involved 32 students of Chemistry Education study program. The instrument used to measure collaboration skills is an observation sheet rubric, while the instrument used to measure the improvement of student learning outcomes is in the form of multiple choice questions of 20 questions that have been valid and reliable. The results showed that the application of the PjBL learning model using teaching materials developed in accordance with the PjBL learning model can train student collaboration skills with a percentage of 85.42% with a very high category and can improve student learning outcomes of 77.1% with an effective category. This study shows that there is a positive and significant correlation between collaboration skills and improving student learning outcomes in capita selecta courses (sig.2-tailed 0.000